Evaluation of dietary supplementation of black seed (Nigella sativa) on the histological structure of kidney, liver and testis of rabbit bucks - Hammed, O.O.; Amao, O.A; Ademola, S.G.; Okanlawon, E.O.; Matt-Obabu, A.D. (ADAN JOURNAL OF AGRICULTURE, 2025)
This study investigated the histological response of kidney, liver and testis of rabbit buck to dietary supplementation of Black seed (Nigella sativa). Twenty (20) Chinchilla X New Zealand White, 5-6 weeks old, were balanced for weight and assigned to four (4) treatments T1, T2, T3 and T4 of five rabbits each in a Completely Randomized Design (CRD). The four experimental treatments were supplemented with black seed (Nigella sativa) at 0, 0.5, 1.0 and 1.5% levels, respectively. After twelve (12) weeks of feeding, the bucks were sacrificed and organs (kidney, liver and testes) were extracted for histological evaluation. The results showed that kidney tubular system and the interstitium appeared healthy and normal in the treated groups (T2, T3 and T4) with a mild improvement over the control (T1). The liver hepatocytes were also observed to be normal across the treatments. The seminiferous tubules in testes of rabbit bucks fed varying levels of Black seed had normal and larger well-arranged germ cell population than the control. As Nigella sativa supplementation increased up to 1.5%, the testicular histo-architecture remained normal. This study demonstrated that Nigella sativa seeds, at the supplementation levels in diet, possess the potential to improve and preserve the histo-architecture of rabbit kidney, liver and testis